Latihan Range of Motion (ROM) Aktif Meningkatkan Kekuatan Otot Ekstremitas Bawah dan Rentang Gerak Sendi Lansia - Detiana, Detiana; Somad, Abdul; Lusiana, Lusiana (Journal of Telenursing (JOTING), 2023)
This study aims to evaluate the effect of active Range of Motion (ROM) training on increasing lower extremity muscle strength and joint range of motion in the elderly. A total of 55 elderly people who live in the work area of ​​a community health center with complaints of activity disruption were respondents to this study. The research design used was pre-experimental with a one group pretest-posttest design. In the first stage, a pre-test is carried out to assess lower extremity muscle strength and joint range of motion before administering the procedure. Next, the Range of Motion (ROM) exercise is given once, followed by a return measurement after the action. The results of measurements before and after administering the action were analyzed using the Paired T test. It was found that there was a significant increase in lower extremity muscle strength and joint range of motion in the elderly after active ROM training. This shows that active ROM training is effective in increasing muscle strength and joint range of motion in the elderly. It can be concluded that active Range of Motion (ROM) training is an effective method and can be integrated into fitness programs for the elderly to improve muscle health and joint function. Regular implementation of this exercise can be a strategy in promoting the health of the elderly and minimizing the risk of decreased physical function due to aging. Keywords: ROM Training, Muscle Strength, Range of Motion, Degenerative Disorders, Aging